Customary Slaughtering Methods and their Comparison with Islamic Slaughtering (Zabiha) - The Review - Arshad, Muhammad Sajid; Khan, Urooj; Khalid, Waseem (Universitas Islam Indonesia, 2022)
This review investigates about most commonly adopted slaughtering techniques and their comparison with that of the technique, portrayed by Islam. The customary methods of animal slaughtering involve stunning. Ritual kosher which resembles with halal slaughtering method but do not include Tasmiyah, the other one is jhatka slaughtering method which obeys killing of animal by severing the head with single stroke of axe or sword. Whereas, the Islamic slaughtering manner, commonly known as Zabiha, obligates the cut of trachea, food pipe, carotid artery and jugular vein, while reciting the Holy name of Allah. The review framed the documentations of some researches, which clearly reveal that stunning, ritual kosher and jhatka slaughtering cause poor meat quality, highly prone to bacterial attacks, congestion of meat, reduction in shelf life, as well as more the suffering of animal which is clearly against the animal welfare as claimed by some antagonist lobbyists.